2014
DOI: 10.1371/journal.pone.0108529
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Viral Hemorrhagic Septicemia Virus in Marine Fish along the Norwegian Coastal Line

Abstract: Viral hemorrhagic septicemia virus (VHSV) infects a wide range of marine fish species. To study the occurrence of VHSV in wild marine fish populations in Norwegian coastal waters and fjord systems a total of 1927 fish from 39 different species were sampled through 5 research cruises conducted in 2009 to 2011. In total, VHSV was detected by rRT-PCR in twelve samples originating from Atlantic herring (Clupea harengus), haddock (Melanogrammus aeglefinus), whiting (Merlangius merlangus) and silvery pout (Gadiculus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
21
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 45 publications
2
21
0
Order By: Relevance
“…Many wild fish have been reported to be carriers of VHSV, including olive flounder, silver pomfret and so on (Kim et al, ; Lee, Yun, Kim, Jung, & Oh, ), these VHSV‐positive fish had a major role in VHSV transmission. Gills are the main portals to virus entry in the waterborne infections (Carballo et al, ), and it has been demonstrated as an ideal organ for detecting VHSV carrying fish (ohansen et al, ; Sandlund et al, ). Thus, in this study, the kidney, heart, spleen (the prime target organ of VHSV), brain (the potential site for long‐term persistence of VHSV) and gill (the prime port of entry for VHSV) tissues were sampled from different wild fish and tested for VHSV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Many wild fish have been reported to be carriers of VHSV, including olive flounder, silver pomfret and so on (Kim et al, ; Lee, Yun, Kim, Jung, & Oh, ), these VHSV‐positive fish had a major role in VHSV transmission. Gills are the main portals to virus entry in the waterborne infections (Carballo et al, ), and it has been demonstrated as an ideal organ for detecting VHSV carrying fish (ohansen et al, ; Sandlund et al, ). Thus, in this study, the kidney, heart, spleen (the prime target organ of VHSV), brain (the potential site for long‐term persistence of VHSV) and gill (the prime port of entry for VHSV) tissues were sampled from different wild fish and tested for VHSV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Several RT-qPCR assays are available to detect the IHNV or VHSV genome (Cutrín et al, 2009;Garver et al, 2011;Gjevre, Ørpetveit, Tavornpanich, & Lyngstad, 2014;Hope et al, 2010;Jonstrup et al, 2013;Liu et al, 2008;Lopez-Vazquez, Bandín, & Dopazo, 2015;Phelps, Patnayak, Jiang, & Goyal, 2012;Pierce et al, 2013;Purcell et al, 2013;Sandlund et al, 2014;Warg et al, 2014aWarg et al, , 2014b. However, diagnostic performance of most IHNV and VHSV RT-qPCR assays has not been fully evaluated in accordance with OIE guidelines (Bustin et al, 2009;Jonstrup et al, 2013;OIE, 2017d;Warg et al, 2014a).…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that testing gills might detect more positive samples than testing internal organs. However, it has to be acknowledged that positive gills may either reflect true infection or virus being passively carried in the gill mucus (Sandlund et al., ) and hence are not suitable for diagnostic purposes.…”
Section: Discussionmentioning
confidence: 99%